2016
DOI: 10.1289/ehp176
|View full text |Cite
|
Sign up to set email alerts
|

U-Shaped Association between Plasma Manganese Levels and Type 2 Diabetes

Abstract: Background:Manganese is both an essential element and a known toxicant, and it plays important roles in many mechanisms in relation to type 2 diabetes (T2D). However, epidemiological studies of this relationship are rare.Objective:We investigated the association between plasma manganese and newly diagnosed T2D as well as whether the association could be modified by manganese superoxide dismutase (MnSOD) polymorphisms.Methods:We conducted a case–control study of 3,228 participants in China: 1,614 T2D patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 58 publications
2
33
1
Order By: Relevance
“…Although previous studies have revealed that TMAO is linked to the development of diabetes in several animal models, no previous epidemiologic study, to our knowledge, has been designed specifically to examine the association between plasma TMAO and type 2 diabetes, with adjustment for other confounding factors. Plasma TMAO concentrations were found to be higher in patients with diabetes with or without cardiovascular comorbidities (5,20,24), but these studies did not investigate the associations between plasma TMAO and type 2 diabetes after adjustment for other confounding factors. Svingen and colleagues (18) found increased plasma TMAO in patients with type 2 diabetes, but no significant association was observed in their investigation.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Although previous studies have revealed that TMAO is linked to the development of diabetes in several animal models, no previous epidemiologic study, to our knowledge, has been designed specifically to examine the association between plasma TMAO and type 2 diabetes, with adjustment for other confounding factors. Plasma TMAO concentrations were found to be higher in patients with diabetes with or without cardiovascular comorbidities (5,20,24), but these studies did not investigate the associations between plasma TMAO and type 2 diabetes after adjustment for other confounding factors. Svingen and colleagues (18) found increased plasma TMAO in patients with type 2 diabetes, but no significant association was observed in their investigation.…”
Section: Discussionmentioning
confidence: 97%
“…In our study medians (IQRs) of plasma TMAO concentration of total samples were 1.55 mmol/L (0.93, 2.45 mmol/L), which were comparable with a study conducted in Austria [1.74 mmol/L (0.38, 3.48 mmol/L)] (23). Plasma TMAO concentrations were reported to be related to genetic predisposition, intake of dietary trimethylamine-containing compounds, intestinal microbiota constitute, FMO activity, health status, other predisposing factors on metabolism of TMAO, and different measurement methods (2,7,20), but the reasons for the wide variations in TMAO concentrations across populations remain to be elucidated. Although previous studies have revealed that TMAO is linked to the development of diabetes in several animal models, no previous epidemiologic study, to our knowledge, has been designed specifically to examine the association between plasma TMAO and type 2 diabetes, with adjustment for other confounding factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma Mn and Mn superoxide dismutase (MnSOD) have been recommended as potential biomarkers for Mn nutritional status in the human body [3], and both of them have been associated with type 2 diabetes. Low serum Mn has been associated with a high risk of type 2 diabetes [8]. However, higher levels of Mn in serum [9] and urine [10,11] have also been reported in individuals with diabetes, and similar wholeblood Mn levels between diabetic and non-diabetic individuals have been observed [12].…”
Section: Introductionmentioning
confidence: 96%
“…Alternatively, several TE can affect the process of aging [6] by contributing to numerous age-related mechanisms, via, for example, their role in the immune system or against oxidative stress. They have been, therefore, hypothesized to contribute to the pathogenesis of age-related chronic diseases [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%